1997
DOI: 10.1007/s003920050085
|View full text |Cite
|
Sign up to set email alerts
|

Kardiovaskuläre Fehlbildungen in Bayern 1984–1991 (Cardiovascular malformations in Bavaria, Germany, 1984–1991)

Abstract: The study presents data on cardiovascular malformations in Bavarian livebirths, born between 1984 and 1991. Cases have been ascertained retrospectively by reviewing hospital records of all children being referred to a children's hospital up to 2 years of age. The classification scheme was based on abnormalities in developmental mechanisms. Among 984,570 livebirths, 7020 cases with structural congenital heart disease were identified. The birth prevalence was 7.1 per 1000 livebirths. Between 1984 and 1991, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
4
1
1
Order By: Relevance
“…In comparison with the CVA prevalence of the general population (0.62%), Bavarian children seem to be at lower risk than the Canadian population (2%). 9,13 Thus, RR of the Italian study calculated on the basis of the Canadian data may not be comparable with ours. However, the incidence of bicuspid aortic valves was very low among Bavarian children compared with more current studies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In comparison with the CVA prevalence of the general population (0.62%), Bavarian children seem to be at lower risk than the Canadian population (2%). 9,13 Thus, RR of the Italian study calculated on the basis of the Canadian data may not be comparable with ours. However, the incidence of bicuspid aortic valves was very low among Bavarian children compared with more current studies.…”
Section: Discussioncontrasting
confidence: 57%
“…The CVA prevalence in UTS revealed in the Bavarian study, in which data of almost one million children had been analyzed, was 33.3%. 9 Thus, in comparison with this almost unbiased study, our prevalence is within the same dimension, assuming the bias of our study is negligible.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This situation will likely worsen; an analysis performed by the German National Registry for CHD showed that the prevalence of severe CHD has steadily increased since 2008 [26]. Therefore, ACHD severity in primary care will likely increase in upcoming decades, and many ACHD are likely to suffer from severe CHD residua and sequelae [2].…”
Section: Medical Care For Achd In Germany From the Pcp's Perspectivementioning
confidence: 99%
“…Congenital heart defect (CHD), the most common isolated congenital organ abnormality, is defined as any type of congenital defect in one or more structures of the heart or blood vessels or a hereditary disorder involving the heart or the great vessels (e.g., Marfan Syndrome or Fabry disease) [1,2].…”
Section: Introductionmentioning
confidence: 99%